2009
DOI: 10.21273/hortsci.44.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Potential Vegetative and Floral Production and Fruit Characteristics of Watermelon Pollenizers

Abstract: Triploid (seedless) watermelon [Citrullus lanatus (Thunb.) Matsum. and Nak.] pollen is nonviable; thus, diploid (pollenizer) watermelon cultigens are required to supply viable pollen for triploid watermelon fruit set. The objective of this research was to characterize maximum potential vegetative growth, staminate and pistillate flower production over time, and measure exterior and interior fruit characteristics of pollenizer cultigens. Sixteen commercially available and numbered line (hereafter collectively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 16 publications
4
15
0
Order By: Relevance
“…2A and 3A), it might not be the optimum pollenizer. The number of flowers per plant shows a similar pattern as was observed in previous studies (Dittmar et al, 2009;, although a lower absolute number of flowers was observed in the current study. The data for the number of pistillate flowers are not shown.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…2A and 3A), it might not be the optimum pollenizer. The number of flowers per plant shows a similar pattern as was observed in previous studies (Dittmar et al, 2009;, although a lower absolute number of flowers was observed in the current study. The data for the number of pistillate flowers are not shown.…”
Section: Resultssupporting
confidence: 91%
“…The current study focused on early flowering and specifically aims to make recommendations for synchronization of pollenizer flowering patterns with the peak period of triploid pistillate flowering. However, growers may want to extend the length of the harvesting window and that would require pollenizer cultivars that flower consistently for a long period of time (Dittmar et al, 2009;Maynard and Elmstrom, 1992). At the end of our study at Week 6, most of the pollenizer plants were still flowering at a high level and other studies have shown that the number of flowers per plant is still increasing at this stage (Dittmar et al, 2009;.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…The pots were spaced 0.8 m between rows and 0.4 m between plants. A 3:1 ratio between triploid and diploid varieties was used in dedicated rows (Fiacchino & Walters, 2003;Dittmar et al, 2009) for seedless watermelon cultivation. Plants were trellised to facilitate management of this crop in a protected environment greenhouse.…”
Section: Site and Agricultural Practicesmentioning
confidence: 99%